CHRNA4 rs1044396 is associated with smoking cessation in varenicline therapy - Rocha Santos, Juliana; Tomaz, Paulo R. X.; Issa, Jaqueline S.; Abe, Tânia O.; Krieger, José E.; Pereira, Alexandre C.; Santos, Paulo C. J. L. (Frontiers in Genetics, 2015)
The large individual variability in response to drugs for smoking cessation suggests that specific treatments can be more effective in particular subgroups of smokers. In the context of personalized medicine, the main aim of the present study was to evaluate whether the CHRNA4 and CHRNB2 polymorphisms are associated with response to smoking cessation therapies in patients from a smoker assistance program. This cohort study enrolled 483 smoking patients who received behavioral counseling and drug treatment (varenicline, bupropion and/or nicotine replacement therapy). Smoking cessation success was considered for patients who completed 6 months of continuous abstinence. Fagerström test for nicotine dependence (FTND) and Issa situational smoking scores were analyzed for nicotine dependence. The CHRNA4 (rs1044396 and rs2236196) and CHRNB2 (rs2072660 and rs2072661) polymorphisms were genotyped by high resolution melting analysis.Patients with rs1044396 CC genotype had lower success rate in treatment with varenicline (29.5%) compared with carriers of CT or TT genotypes (50.9%) (p=0.007, n=167). The CT or TT genotypes were associated with higher odds ratio for success (OR=1.67, 95%CI=1.10-2.53, p=0.02), in a multivariate model. We did not observe significant differences in the FTND and Issa scores according to the studied polymorphisms. In conclusion, the CHRNA4 rs1044396 is associated with smoking cessation in individuals on varenicline therapy. We suggest that this polymorphism influences the varenicline response, but replications of this finding are needed.